2011
DOI: 10.4085/1062-6050-46.6.615
|View full text |Cite
|
Sign up to set email alerts
|

Quadriceps Function After Exercise in Patients with Anterior Cruciate Ligament–Reconstructed Knees Wearing Knee Braces

Abstract: The decrease in T(MVIC) immediately after brace application was not accompanied by differences between bracing conditions. Wearing a knee brace or neoprene sleeve did not seem to affect the deterioration of quadriceps function after aerobic exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Neither study demonstrated a benefit over placebo for any outcome measure. A trial of 14 patients following ACLR randomised patients to receive either a knee brace, neoprene sleeve or no brace 31. No differences were observed between brace and no-brace conditions after aerobic exercise.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither study demonstrated a benefit over placebo for any outcome measure. A trial of 14 patients following ACLR randomised patients to receive either a knee brace, neoprene sleeve or no brace 31. No differences were observed between brace and no-brace conditions after aerobic exercise.…”
Section: Resultsmentioning
confidence: 99%
“…Other therapies including TMS,28 taping,29 30 bracing,31 application of heat34 and soft tissue release strategies32 were of no clinical benefit in the management of AMI.…”
Section: Discussionmentioning
confidence: 99%
“…60 We found that graft type did not affect excitability, but future prospective studies using more specific time points for data collection may allow for the evaluation of additional covariates that may improve our understanding of factors that influence neuromuscular alterations after ACL-R. Researchers have indicated that the use of a knee brace may alter voluntary quadriceps activation 61,62 ; given that we did not allow braces to be worn during testing, we do not know whether periodic brace use during activities outside of testing may have influenced lasting alterations in neuromuscular measurements.…”
Section: Discussionmentioning
confidence: 86%
“…Previous investigations have used various fatiguing exercise protocols to better understand the effects of simulated athletic participation in healthy 10,[15][16][17][18][19][20] and pathological populations. [21][22][23][24] Lower extremity muscles become weaker and more inhibited after prolonged exercise in healthy individuals. 10,17,23 In healthy individuals, decreased quadriceps strength and altered gait biomechanics have been measured after isokinetic fatigue of the hamstrings and quadriceps.…”
mentioning
confidence: 99%